(untitled) (Fiep Bulletin - online, 2014)
The proposal of this investigation and intervention is to take the game as privileged pedagogic resource for the children education. It is justified because the necessity of new practices that assumes the games as an important theme in education. The research establishes as central objectives to contribute in the process of the academical students’ initial formation and school teachers continuum’ formation and still to produce knowledge about and from the education context. The methodology is the actionresearch and the procedures consist in meetings, dialogues and seminars among the participants of the collective research to study on the theoretical support and planning the actions that will be developed inside the school partnership. The collective (academics and teachers) share all the experiences at school and the theoretical support that is based, especially, in the Historical-cultural Theory. The actions at school are planed and built for all participants and it becomes the subject for the process’ analysis and discussions. The results and relevant data are related in a diary that becomes the evaluation sources, formation and scientific production. We pointed so far a new direction for the participant teachers’ conception, because the playing’ activities start to be valorized in the process of the children’s education. The students of Physical Education and Pedagogy courses who participated in this project are members of the Research Group called “Cultura Corporal: sabers e fazeres” and they are having important opportunities to see and work with the reality, linking all the time theory and practices, trying to get over the historical dichotomies among theory-practice, Higher education-Basic Education, work-games and to solve the historical educational problems of pedagogical practices.